Agribisnis Tembakau di Indonesia : Kontroversi dan Prospek - Muchjidin Rachmat; Rizma Aldillah (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2010)
EnglishTobacco is one of the important commodities in Indonesia. The tobacco industry contributes significantly to the Indonesian economy, especially tax and excise as a source of government income, employment opportunity, source of income and regional development. However, tobacco and cigarettes has a negative impact on health and the environment. Indonesian cigarette industry is in a dilemma situation. Increasing public awareness about health and anti-smoking cigarettes causes a decrease of tobacco demand in the world and Indonesia, and its negative impact in the demand for tobacco leaf. This condition must be anticipated at the early stage with directive program in the development of tobacco crop substitution. This substitution can be carried out through the development of high value alternative crops with the application of technology and market assurances. Among these high value commodities are horticultural crops, like vegetables and ornamental plants. To ensure market and the application of technology for such crops, it is necessary to develop a partnership relation with the market actors. With a large number of smokers and a hereditary culture, Indonesia is considered as a potential market for the tobacco industry. This condition should allow a greater negative impact and social costs for Indonesia. To encounter such situation, Indonesia need a cigarette consumption reduction policy which could be applied through: (a) high cigarette tax and price, (b) strictly abandon promotion, advertisement and cigarette sponsorship in various events that involve young people, and (c) well-guarded stipulation on free smoking area.IndonesianTembakau merupakan salah satu komoditas penting di Indonesia. Industri tembakau memberikan kontribusi yang signifikan bagi perekonomian Indonesia, terutama cukai dan devisa sebagai sumber penerimaan negara, lapangan kerja, sumber pendapatan dan pembangunan daerah. Namun, tembakau dan rokok memiliki dampak negatif terhadap kesehatan dan lingkungan. Industri rokok Indonesia berada dalam situasi dilema. Peningkatan kepedulian masyarakat tentang kesehatan dan gerakan anti-merokok menyebabkan penurunan permintaan dunia dan Indonesia pada rokok, dan berdampak kepada penurunan permintaan daun tembakau. Kondisi ini harus diantisipasi secara dini dan terprogram dalam bentuk pengembangan tanaman substitusi tembakau. Upaya substitusi ini dapat dilakukan melalui pengembangan tanaman alternatif bernilai ekonomi tinggi dengan penerapan teknologi dan jaminan pasar. Beberapa komoditas bernilai tinggi tersebut terutama tanaman hortikultura, seperti sayuran dan tanaman hias. Untuk memberikan kepastian pasar dan penerapan teknologi perlu dikembangkan pola kemitraan dengan pelaku pasar. Dengan jumlah penduduk yang besar dan memiliki budaya merokok yang turun temurun, Indonesia dinilai merupakan pasar yang potensial bagi industri rokok. Kondisi ini akan berakibat Indonesia akan menerima lebih besar dampak negatif dan biaya sosial. Untuk itu diperlukan kebijakan pengurangan konsumsi rokok melalui: (a) peningkatan cukai dan harga rokok, (b) pengendalian/pelarangan iklan dan sponsor rokok dalam kegiatan yang melibatkan remaja, dan (c) penetapan kawasan bebas rokok.